Fables. Volume one : the wolf among us - Sturges, Lilah; Justus, Dave (DC Comics ; Vertigo Comics, 2015)
Bigby Wolf used to break every law in the books. Now, as the sheriff of Fabletown---New York City's magically concealed neighborhood of mythical, legendary and fairy tale figures--he is the law, and keeping the streets safe for Fables and Mundanes alike is his beat. So when a beautiful princess-turned-prostitute is decapitated on his watch, Bigby must unleash the wolf within to catch the killer. With the help of Snow White, his only friend, and Mayor Ichabod Crane, his longtime enemy, Bigby must crack the case soon. He may be the law, but some people can't wait to break him.